View of knowledge flow description - Khalefa, Mustafa S.; A. Jabar, Marzanah; Abdullah, Rusli; Abdullah, Salfarina; Gheni, Ali Yahya (American-Eurasian Network for Scientific Information, 2015)
Knowledge flow exists in very nearly in each teamwork, community cooperation environment and now it attracts much consideration, attention in the knowledge management field. In a knowledge-based organization, knowledge workers need to acquire a variety of knowledge (information) about their tasks .Therefore; many organizations have built knowledge support plat forms to assist workers in meeting their knowledge-needs. These platforms help workers to identify and share knowledge in order to speed up organization innovation and improve employee Productivity. The paper gives an over view of knowledge flow, type of knowledge flow, mechanical of knowledge flow, knowledge flow process. This review shows the description of Knowledge flow element and knowledge characteristic. This paper as systematic review of the knowledge flow. Choose the best way according to that.